The strike wings special anti-shipping squadrons, 1942-45 - Nesbit, Roy Conyers (HMSO, 1995)
In 1942 the RAF began to form special Strike Wings to attack the heavily defended and seemingly invulnerable convoys that brought Germany's vital supplies down the coast of Europe. The outcome was a series of air/sea battles at close quarters, fought with increasing intensity until the last days of the war.